Eficácia do tratamento não-cirúrgico em indivíduos com mucosite peri-implantar - Menezes, Karyna de Melo (2014)
It has been shown that the development of peri-implant mucositis is associated with biofilm accumulation. It is believed that the therapeutic approaches used in periodontal disease may have a positive effect in the cases of peri-implant disease. The aim of this study was to evaluate the effectiveness of non-surgical treatment of peri-implant mucositis, with or without the use of chlorhexidine 0,12% in subjects rehabilitated with osseointegrated implants. Thus, patients were randomly divided into test group (chlorhexidine surgical therapy) and control (non-surgical treatment). This therapy consisted of an adaptation of the (Full Mouth scalling and Root Planing) nonoperative protocol FMSRP, but without the use of ultrasound. The visible plaque index (VPI), gingival bleeding index (GBI), probing depth (PD), bleeding on probing (BOP) and keratinized mucosa clinical parameters were evaluated at baseline and at different times after treatment. The data were not normally distributed and the implant was considered the sampling unit. Data were analyzed using Fri edman and Wilcoxon chi-square (=5%), tests using the Statistical Package for Social Sciences 17.0 (SPSS). Thus, 119 implants were evaluated, 61 in the test group and 58 in the control group. The results showed statistically significant differences for the variables: average BTI implants in both groups (p<0,001), mean ISG implants both in the test group (p<0,001), and control (p= 0,006) of implants; PS for the test group (p< 0,001) and control (p = 0,015) and SS (p<0,001) in the two treatment groups. However, there was no statistically significant difference when the groups were compared. The PS and SS variables showed no statistically significant difference in any of independent interest to the study (age, sex, smoking, treatment group, keratinized mucosa at different times, peri-implant biotype, average VPI implants and GBI). Thus, it can be concluded that both the mechanical treatment isolated as its association with chlorhexidine mouthwash 0.12% can be used for the treatment of peri-implant mucositis. Moreover, the condition of oral h ygiene has improved between baseline and six months and the depth and bleeding on probing decreased after three and six months